2013
DOI: 10.1007/s12306-013-0266-z
|View full text |Cite
|
Sign up to set email alerts
|

Treatment for proximal humeral fractures with percutaneous plating: our first results

Abstract: Percutaneous plating of proximal humeral fractures with NCB-PH plate has demonstrated to be a good strategy in managing these lesions without increasing complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
0
4
0
1
Order By: Relevance
“…Procedures using closed reduction are of course less invasive, but it is more difficult to achieve good reconstruction. On the other side, open techniques are more likely to obtain anatomical reduction and stronger fixation, but they present a higher rate of complications related to complete or partial necrosis of the humeral head, regardless of the implant used [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Procedures using closed reduction are of course less invasive, but it is more difficult to achieve good reconstruction. On the other side, open techniques are more likely to obtain anatomical reduction and stronger fixation, but they present a higher rate of complications related to complete or partial necrosis of the humeral head, regardless of the implant used [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although proximal humeral fractures are common lesions of the elderly, accounting for 5% of all fractures and 45% of all humeral fractures [ 1 - 3 ], there is no consensus regarding their treatment. The majority of patients suffering this injury have nondisplaced or minimally displaced two- or three-part fractures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 10 However, some authors have already demonstrated safety of the anterolateral approach as well as the low chance of axillary nerve injury. 10 12 Moreover, this approach facilitates exposure of the lateral humeral surface and identification of major tuberosity fractures that are subsequently dislocated. 10 …”
Section: Discussionmentioning
confidence: 99%
“…Biomechanisch werden deutliche theoretische Vorteile beschrieben, welche jedoch in prospektiv randomisierten Studien klinisch nicht reproduzierbar waren[9]. In einer retrospektiven Studie mit einer kleinen Patientenzahl werden ein gutes Ergebnis, keine Schraubendislokation, keine Humeruskopfnekrose, regelrechte Konsolidierung und ein geringer Weichteilschaden beschrieben[11].…”
unclassified